O processo de agencificação no Brasil: divergência ou mimetismo? - Holperin, Michelle Moretzsohn (2012)
The present study analyses the diffusion of independent regulatory agencies in Brazil, also known as agencification process, in order to verify whether this process was convergent or divergent according to two competing theoretical perspectives. To this end, three mechanisms of diffusion are investigated – political nature, top-down and horizontal – and relevant contextual variables are identified – such as the apparent turmoil between management flexibility and regulation, regulatory federalism, the presence of strongly articulated societal actors and the importance of trade-worthy coalition goods in Brazil‟s multi-party presidentialism that took place in the Brazilian process of agencification. The peculiarities of the Brazilian case, such as the creation of an independent agency for the film industry and the state-level changes that took place indicate the existence of a 'diffusion without convergence', or 'divergent convergence' since, while Brazil has experienced a regulatory agency 'boom', agencies were modeled according to local needs and the specificities of the national context.